EFFECT OF DECENTRALIZATION CONTROL SYSTEM ON THE PERFORMANCE OF MANAGERIAL ACCOUNTING AT PINTU MAS MULIA KIMIA GROUP - One, Jumedi; one, Drs. Supardi, MM.; Nawarcono, SE., MM, Winanto (Accounting, 2009)
The purpose of this study was to determine the effect of Decentralized Control System on Managerial Performance in Accounting PT. Pintu Mas Mulia Kimia Group. Data collected from the Head Office and branch offices in 7 PT. Pintu Mas Mulia Kimia Group taken as Stratified Random Sampling by the number of respondents was 227 persons. Of the 227 respondents, which was worth only 225 respondents were analyzed. To measure the influence of Decentralized Control Systems Accounting used a questionnaire with 10 items of questions, with a value of α = 0.855, Budget Decentralisation used a questionnaire with 8 items of questions, with a value of α = 0.802, and Managerial Performance used a questionnaire with 9 items of questions, with a value of α = 0.789 . The data analysis technique is regression analysis SPSS for windows ver.12 has been used in examining the influence of Decentralized Control System for Accounting and Budget Decentralization on Managerial Performance. The results showed as follows: (1) Decentralization of Accounting Control System has positive and significant impact on Managerial Performance is indicated by p value or significance probability of 0.002 (